PROSECUTING ACTS OF TERRORISM AS CRIMES AGAINST HUMANITY UNDER THE ICC TREATY - Galingging, Ridarson (UI Scholars Hub, 2010)
This article explores the possibility of prosecuting terrorism as crimes against humanity under the ICC treaty. Even-though terrorism is not explicitly mentioned as a crime that falls under the jurisdiction of the International Criminal Court, it can however be adjudicated at the ICC by interpreting it as included in Article 7 of the Rome Statute. Article 7 of the ICC Statute can be used as a legal basis for prosecuting terrorist acts if the acts fulfill the Article’s general requirements. The text of the Rome Statute does not need to be amended in order to encompass acts of terrorism.